BAKTERI ASSOSIASI DI KARANG BATU (Skleractinian) YANG TERINFEKSI PENYAKIT TUMOR (Growth Anomalies) YANG BERASAL DARI PULAU SALEMO KABUPATEN PANGKEP - Massinai, Arniati; Tahir, Akbar; Jompa, Jamaluddin; Rantetondok, Alexander (Hasanuddin University, 2017)
Coral disease is one of the threats to the health of coral but is not yet widely known. This study was conducted todetermine the types of bacterial associations in hard corals infected with growth anomaly (GA). Coral samplesinfected with GA disease were taken by using SCUBA tool on Salemo Island, Mattiro Bombang Village, PangkepDistrict. Bacterial isolation was performed by removing mucus from corals infected by growth anomaly by 1ml and diluted to dilution 10-3 . Purification of bacteria is done by inoculating the solid medium of Marine Agar.Furthermore, Gram staining and biochemical tests were performed. Bacterial identification was performed basedon colony morphology and biochemical reaction test results. The results showed that GA disease can infectcoral Porites, Acropora digitate, Platygyra and pocillopora . Bacteria are found from the genus Flavobacterium,Acinetobacter and, Neiseria. Keywords: Bacteria association, coral stone, coral disease, growth anomaly